Probiotic Supplements: Hope or Hype? - Wang, Yuxuan; Jiang, Yinyin; Deng, Yuxin; Yi, Chen; Wang, Yangcan; Ding, Mengnan; Liu, Jie; Jin, Xuanjing; Shen, Lishan; He, Yue; Wu, Xinyun; Chen, Xuefei; et al. (Frontiers in Microbiology, 2020)
Probiotic bacteria have been associated with various health benefits and included in overwhelming number of foods. Today, probiotic supplements are consumed with increasing regularity and records a rapidly growing economic value. With billions of heterogenous populations of probiotics per serving, probiotic supplements contain the largest quantity of probiotics across all functional foods. They often carry antibiotic resistant determinants that can be transferred to and accumulate in resident bacteria of the gastrointestinal tract and risking their acquisitions by opportunistic pathogens. While the health benefits of probiotics have been widely publicized, this health risk is however under-represented in both scientific studies and public awareness. On the other hand, the human gut presents conditions that are unfavorable for bacteria, probiotics included. It remains uncertain if probiotics from supplements can tolerate acids and bile salts that may undermine their effectiveness in conferring health benefits. Here, we put into perspective the perceived health benefits and the long-term safety of consuming probiotic supplements specifically bringing the intolerance to acids and bile salts, and the long-standing issue of antibiotic resistant gene transfer into sharp focus. We report that probiotics from supplements examined in this study have poor tolerance to acids and bile salts while also displaying resistance to multiple antibiotics. They could also adapt and gain resistance to streptomycin in vitro. In an environment where consuming supplements is considered a norm, our results and that of others will put in perspective the persisting concerns surrounding probiotic supplements so that the current hype doesn’t overpower the hope.